TRPC3 governs the spatiotemporal organization of cellular Ca2+ signatures by functional coupling to IP3 receptors. (December 2022) - Curcic, Sanja; Erkan-Candag, Hazel; Pilic, Johannes; Malli, Roland; Wiedner, Patrick; Tiapko, Oleksandra; Groschner, Klaus
Highlights: TRPC3 shares a common Ca 2+ signaling microdomain with IP3 receptors. TRPC3-mediated Ca 2+ entry suppresses microdomain Ca 2+ spiking and oscillations. TRPC3 is transiently targeted into ER-plasma membrane junctions to communicate with IP3 receptors in a dynamic manner. TRPC3 activity states govern spatiotemporal Ca 2+ signaling signatures. Abstract: Communication between TRPC channels and IP3 receptors (IP3 R) is considered pivotal in the generation of spatiotemporal Ca 2+ signaling patterns. Here we revisited the role of TRPC3-IP3 R coupling for local Ca 2+ signaling within TRPC3-harbouring micro/nanodomains using R-GECO as a reporter, fused to the channel´s C-terminus. Cytoplasmic Ca 2+ changes at TRPC3 originated from both the entry of Ca 2+ through the TRPC channel and Ca 2+ mobilization via IP3 R. Local Ca 2+ changes at TRPC3 channels expressed in HEK293 cells were predominantly biphasic with IP3 R-dependent initial Ca 2+ transients, while exclusively monophasic signals were recorded when all three IP3 R isoforms were lacking. Abrogation of Ca 2+ entry through TRPC3 by point mutations, which impair Ca 2+ permeability (E630Q), cation permeation (E630K), or DAG sensitivity (G652A), promoted microdomain Ca 2+ oscillations. Ca 2+ signals at E630Q, E630K, and G652A channels featured initial Ca 2+ transients along with oscillatory activity. Similarly, when extracellular Ca 2+ was omitted, IP3 R-mediated Ca 2+ transients and Ca 2+ oscillations were promoted at the cytoplasmic face of wild-type TRPC3 channels. By contrast, oscillations, as well as initial Ca 2+ transients, were virtually lacking, when the TRPC3 channels were sensitized by preexposure to low-level PLC activity. TIRF imaging provided evidence for dynamic colocalization of TRPC3 and IP3 R. We suggest that TRPC3-mediated Ca 2+ entry controls IP3 R activity at ER-PM junctions to determine Ca 2+ signaling signatures and enable specificity of downstream signaling. Graphical abstract: Image, graphical abstract